A method for preparing a PEM water electrolysis membrane electrode

The anode diffusion layer is prepared by using rutile titanium dioxide nanotubes as support materials and traditional papermaking molding process, and the catalyst network structure is formed by impregnating precious metal solutions and high-temperature oxidation, which solves the high cost and unstable performance of the existing PEM water electrolytic membrane electrode. Problem, low-cost and high-performance membrane electrode preparation is achieved.

CN116043254BActive Publication Date: 2025-02-14SHANGHAI BRIGHT-H TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310024374.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-06
Publication Date
2025-02-14
Estimated Expiration
2043-01-06

AI Technical Summary

Technical Problem

The existing PEM water electrolytic membrane electrodes have problems such as high cost, unstable performance, and catalyst shedding in the preparation process of the anode diffusion layer and membrane electrode, which limits their industrial applications.

Method used

Using non-conductive titanium dioxide nanotubes as support material, it is converted into rutile titanium dioxide nanotubes through high-temperature calcination, combined with traditional papermaking molding process to prepare the anode diffusion layer, and then form a catalyst network structure by impregnating precious metal solutions and high-temperature oxidation, and finally exchange it with protons. Film composite roller pressing to prepare film electrodes.

Benefits of technology

A low-cost, high chemical stability and high conductivity anode diffusion layer is achieved, avoiding the use of precious metal plating, reducing the overall cost and thickness of the film electrode, and improving the utilization rate of catalytic reactions and the stability of the film electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116043254B_ABST
    Figure CN116043254B_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a PEM water electrolysis membrane electrode, which relates to the field of PEM water electrolysis hydrogen production. Titanium dioxide nanotubes are used as supporting materials to prepare an anode diffusion layer. Because the tube structure has high gas and liquid conductivity, it is beneficial to the separation of oxygen and water in the water electrolysis process. The titanium dioxide nanotubes are calcined at high temperature to transform into a rutile lattice structure, which has high conductivity and stability. The anode diffusion layer is prepared by stacking multiple thin single-layer supporting layers, and the porosity can be controlled within a suitable range. The anode diffusion layer has higher mechanical strength, plays a supporting role, meets the mechanical strength requirements of the water electrolyzer during operation, has higher porosity, and can effectively improve the transmission of water and gas between layers. The precious metal undergoes a solid phase reaction to be embedded in the surface of the rutile titanium dioxide nanotubes to form a dense catalytic conductive network structure, which is not easy to fall off, and can realize the batch preparation of membrane electrodes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of PEM water electrolysis hydrogen production, and in particular relates to a method for preparing a PEM water electrolysis membrane electrode. Background Art

[0002] Hydrogen energy is regarded as the most promising clean energy in the 21st century. It has the characteristics of wide sources, clean and carbon-free, flexible and efficient, and rich downstream application scenarios. Through the "electricity-hydrogen-electricity" conversion method, the optimal solution for long-term or seasonal power reserve is formed. It is a new energy storage method and realizes zero carbon emissions in the whole process of power generation, storage and use. From the perspective of safety and efficiency, hydrogen energy promotes the development of renewable energy, effectively reduces my country's dependence on imports in the fields of oil and natural gas, and at the same time alleviates the problem of spatial mismatch between my country's power supply side and load side through the form of electric hydrogen coupling, promotes the balance between energy supply and consumption areas, and improves the safety and operation efficiency of my country's energy system. With the continuous deepening of domestic green environmental protection work, hydrogen energy has great potential as an ideal clean energy in the future, and the demand for hydrogen will continue to increase. PEM water electrolysis technology can use excess electricity from renewable energy such as wind and light to electrolyze hydrogen, while alleviating the pressure on the power grid. PEM water electrolysis hydrogen production has many advantages. In the hydrogen production process, only water is needed as raw material, the product hydrogen and oxygen are of high purity, and the hydrogen and oxygen interpenetration is slight. The electrolysis process is efficient, safe, non-toxic and harmless, the equipment has a compact structure, and can achieve on-site hydrogen production.

[0003] PEM water electrolysis has become one of the most ideal hydrogen production methods due to its high electrolysis efficiency, resistance to power fluctuations and high purity of hydrogen production, and has attracted widespread attention from scientific research institutions and manufacturers in various countries. At present, the United States, Germany and other countries have commercial products of large-scale electrolyzers of megawatt level. However, due to the high cost and process, the large-scale application of PEM electrolyzers is limited. The anode diffusion layer is one of the key technologies in PEM water electrolysis technology. It plays the role of conducting electricity, separating water flow and air flow, and supporting in the PEM water electrolysis cell. Therefore, there are very high requirements for the mechanical properties, conductive properties, chemical stability, cost and other aspects of the anode diffusion layer material. Its cost accounts for a large part of the various components of the PEM stack. The research on low-cost, high chemical stability and high conductivity anode diffusion layer is of great significance.

[0004] When the electrolysis reaction is carried out in the PEM electrolytic cell, the anode of the electrolytic cell is in an acidic environment, and the electrolysis voltage is usually higher than 1.6V. Therefore, a titanium material with good stability must be selected as the anode diffusion layer. At present, for the anode diffusion layer of the PEM electrolytic cell, the materials selected are mostly porous titanium materials, such as the commonly used porous sintered titanium plates and titanium fiber felts. Their pore structure can meet the mass transfer needs of the PEM electrolytic cell and achieve higher electrolysis performance, but untreated metallic titanium will form a layer of titanium dioxide film on the surface in an oxidizing environment, resulting in a significant decrease in conductivity. In order to maintain its high electrical conductivity, it is usually necessary to plate precious metals such as platinum on the surface of the sintered titanium plate or titanium fiber felt for corrosion protection, but this treatment method also makes the anode diffusion layer costly and cannot be achieved in industrial mass production. To solve this problem, some researchers have magnetron sputtered a layer of platinum on the surface of a porous sintered titanium plate, or magnetron sputtered a layer of platinum on the titanium fiber felt. Sputtering a thin layer of iridium to achieve anti-corrosion and anti-oxidation functions. Although these methods reduce the amount of precious metals used to a certain extent, the preparation process is complicated and the thin layer of iridium formed by sputtering is unstable and easily falls off during the reaction. Therefore, there are still problems such as poor stability and slow preparation efficiency.

[0005] In addition, the membrane electrode for PEM electrolyzer is the core component of the catalytic reaction, which is composed of a diffusion layer, a catalytic layer, and a proton exchange membrane. In addition to the series of problems with the anode diffusion layer mentioned above, the current mainstream preparation processes for the overall preparation of the membrane electrode are spraying, thermal transfer, and coating. The spraying process is slow in preparing membrane electrodes, and thermal transfer has problems such as catalyst residue. The coating process is highly efficient, but the swelling of the proton exchange membrane has always existed. The problems with these processes also lead to the difficulty in preparing PEM water electrolysis membrane electrodes, large material waste, and high cost. In addition, due to the high metal loading of the catalyst layer, during actual operation, it is easy to cause the catalyst to fall off due to mechanical force, pressure, and high and low temperature stress changes, which seriously affects its industrial use.

[0006] In summary, with the rapid development of PEM water electrolysis today, how to solve the balance problem between cost and performance in the anode diffusion layer and realize the mass production of membrane electrodes are the key to our research. Summary of the invention

[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide a method for preparing a PEM water electrolysis membrane electrode to solve the problems raised in the above background technology.

[0008] To achieve the above object, the present invention provides a method for preparing a PEM water electrolysis membrane electrode, comprising the following steps:

[0009] Step 1: Cleaning the titanium dioxide nanotubes;

[0010] Step 2: chopping the titanium dioxide nanotubes cleaned in step 1 into short pieces, and then calcining them in an inert gas atmosphere to form rutile titanium dioxide nanotubes;

[0011] Step 3: Put the rutile titanium dioxide nanotubes into a container, add a dispersant, a binder and deionized water, and perform ultrasonic dispersion to obtain a rutile titanium dioxide nanotube slurry;

[0012] Step 4: using a papermaking process to shape the rutile titanium dioxide nanotube slurry obtained in step 3 to prepare a rutile titanium dioxide nanotube fiber base paper, and forming a rutile titanium dioxide nanotube fiber layer after drying;

[0013] Step 5: dissolving hexahydrated iridium chloride H2IrCl6·6H2O and trihydrated ruthenium chloride RuCl3·3H2O in deionized water to obtain a precious metal solution, placing the rutile titanium dioxide nanotube fiber layer obtained in step 4 into the precious metal solution, adding an alkaline solution, controlling the pH to be greater than 7, removing the fiber layer after immersion, and stacking the impregnated single-layer rutile titanium dioxide nanotube fiber layer in N layers, where N is greater than 1. After stacking, pressurizing the fiber layer and placing the fiber layer in an oxygen-containing environment for finalizing and calcining to form a current collecting layer having a catalyst layer of a mixture of iridium oxide and ruthenium oxide;

[0014] Step 6: Composite roll-press the current collecting layer with the iridium oxide and ruthenium oxide mixture catalyst layer obtained in step 5 and the proton exchange membrane with the catalyst layer at the cathode (assuming that the cathode already has a diffusion layer) to obtain a PEM water electrolysis membrane electrode with a current collecting layer at the anode.

[0015] In the field of PEM water electrolysis, the gas diffusion layer is generally called the current collecting layer. This is determined by the properties of the diffusion layer, which are conductivity and mass transfer. The diffusion layer itself is conductive, so it is also called the current collecting layer.

[0016] Furthermore, in step 1, the specific steps of cleaning the titanium dioxide nanotubes are:

[0017] (1) preparing a hydrochloric acid solution with a concentration of 10-25wt.%;

[0018] (2) placing the titanium dioxide nanotubes in a hydrochloric acid solution, intermittently sonicating for 10-30 minutes, with an intermittent frequency of 2 minutes of sonication, and standing for 1 minute;

[0019] (3) Soaking the titanium dioxide nanotubes after ultrasonic pickling in deionized water for 3-5 times, and rinsing them in running deionized water for 3-5 minutes;

[0020] (4) Soaking the cleaned titanium dioxide nanotubes in an alcohol solvent to prevent contamination; the alcohol solvent is methanol, ethanol or n-propanol.

[0021] Furthermore, the diameter of the titanium dioxide nanotubes is 20-50nm; in step 2, the titanium dioxide nanotubes cleaned in step 1 are placed in a high-speed cutting machine for high-speed short cutting, and the length of the short-cut titanium dioxide nanotubes is 1-5mm; the inert gas is nitrogen, argon or helium; and calcination is carried out in a high-temperature calcination furnace at a calcination temperature of 1200-1500°C for 4-6h.

[0022] Furthermore, in step three, the mass ratio of rutile titanium dioxide nanotubes: dispersant: binder: deionized water is 1:3-8:1-3:15-22; the dispersant is one of ethanol, methanol, n-propanol, isopropanol, and n-butanol, and the binder is 25wt.% PTFE emulsion; and the ultrasonic mixing time is 40-60min.

[0023] Furthermore, in step 4, the wet thickness of the rutile titanium dioxide nanotube fiber base paper is 30-60 μm; the drying temperature is 80-120° C.; the thickness of the rutile titanium dioxide nanotube fiber layer after drying is 10-30 μm, and the porosity is 70-90%.

[0024] Furthermore, in step five, the mass concentration of the precious metal solution is 30-60wt.%, the mass ratio of hexahydrate iridium chloride H2IrCl6·6H2O and trihydrate ruthenium chloride RuCl3·3H2O is 3:1; the alkaline solution is a sodium hydroxide solution with a concentration of 0.5-0.8 mol / L; the pH is controlled at 7.5-8.5; and the immersion time is 10-30 min.

[0025] Furthermore, in step 5, the N value of the single-layer rutile titanium dioxide nanotube fiber layer stacked is 4-7; the shaping calcination temperature is 300-400°C, the calcination time is 2-4h, the pressure is 0.5-2MPa, and the porosity of the prepared collector layer is 60-80%; the loading of metal iridium is 0.8-1.2mg / cm 2 The loading of ruthenium metal is 0.2-0.4 mg / cm 2 ; The flow rate of the oxygen-containing gas is 5-10L / min, and the oxygen-containing environment is an environment filled with air or oxygen.

[0026] Furthermore, in step five, during calcination, the device for providing an oxygen-containing environment for the rutile titanium dioxide nanotube fiber layer after impregnation and stacking is an oxygen-containing calcination platform, and the oxygen-containing calcination platform includes an insulated sealed box with a switch door, and the insulated sealed box is provided with two microporous heating plates arranged parallel to each other, and the microporous heating plates are arrayed with a plurality of ventilation holes, and a storage compartment for the rutile titanium dioxide nanotube fiber layer to be placed in parallel is provided between the two microporous heating plates, and the insulated sealed box is provided with at least two air source pipes connected to the interior of the insulated sealed box, and after the gas in the air source pipes enters the insulated sealed box, it passes through the ventilation holes on the microporous heating plates and acts on the rutile titanium dioxide nanotube fiber layer, so that the rutile titanium dioxide nanotube fiber layer after impregnation and stacking is shaped and calcined in an oxygen-containing environment.

[0027] Furthermore, the microporous heating plate is connected to a transmission main box, a transmission mechanism is provided in the transmission main box, and the microporous heating plate realizes lifting and lowering movement in the heat-insulating sealing box through the transmission mechanism in the transmission main box. The two microporous heating plates are driven by the transmission mechanism to perform lifting and lowering movement in opposite directions, which can increase the space of the storage compartment for the convenience of placing the rutile titanium dioxide nanotube fiber layer; the two microporous heating plates are driven by the transmission mechanism to perform lifting and lowering movement in opposite directions, which can gradually reduce the space of the storage compartment and contact with the rutile titanium dioxide nanotube fiber layer to achieve clamping and hot pressing of the titanium dioxide nanotube fiber layer.

[0028] Furthermore, the transmission mechanism includes but is not limited to a drive motor, a screw rod, and a gear rack transmission group.

[0029] Furthermore, at least two gas source pipelines are provided, and are respectively arranged at the upper top and lower bottom of the heat-insulating sealed box, and are respectively connected to the two microporous heating plates.

[0030] Furthermore, when the two microporous heating plates are clamping and heating the titanium dioxide nanotube fiber layer, there are gaps between the microporous heating plates and the upper and lower inner walls of the heat-insulating sealing box, respectively, to facilitate smooth passage of gas.

[0031] Furthermore, in step six, a short side chain perfluorosulfonic acid resin solution is first prepared, wherein the side chain molecular structure of the short side chain perfluorosulfonic acid resin is one or more of -OCF2CF2SO3H, -OCF2CF2CF2SO3H, and -OCF2SO3H; and the short side chain perfluorosulfonic acid resin solution is sprayed on the surface of the current collecting layer obtained in step five, and then the current collecting layer with the short side chain perfluorosulfonic acid resin solution sprayed on the surface is compositely rolled with the proton exchange membrane having a catalyst layer at the cathode to obtain a PEM water electrolysis membrane electrode having a current collecting layer at the anode.

[0032] Further, in step 6, the concentration of the short side chain perfluorosulfonic acid resin solution is 3-7wt.%; after the short side chain perfluorosulfonic acid resin solution is dried, the resin loading is 6-9mg / cm 2 .

[0033] Furthermore, in step six, the pressure during composite rolling of the current collecting layer and the proton exchange membrane having the catalyst layer at the cathode is 0.3-0.5 MPa.

[0034] Beneficial effects:

[0035] 1. The present invention first uses non-conductive titanium dioxide nanotubes as supporting materials to prepare the anode diffusion layer. On the one hand, the titanium dioxide material is simple and easy to obtain, and will not be oxidized due to long-term exposure to the air, so it has a long service life and a relatively low cost; secondly, due to the existence of the tube structure, the titanium dioxide nanotubes have a "chimney effect" on the conduction of anode oxygen, and have high gas and liquid conduction capabilities, which is conducive to the separation of oxygen and water in the water electrolysis process, and avoids the problem that oxygen cannot be removed to hinder the electrolysis catalysis of water; secondly, compared with the preparation method of sintering titanium plates or titanium fiber felts combined with sputtering precious metals, the present invention can directly change the lattice structure of titanium dioxide itself by high-temperature calcination, and transform it into a rutile lattice structure of titanium dioxide nanotubes. Rutile titanium dioxide has high conductivity and stability, which not only meets the high stability and high conductivity requirements of the PEM water electrolysis anode diffusion layer, but also does not require the plating of precious metal layers, thereby greatly reducing the cost;

[0036] In addition, the present invention adopts a traditional papermaking process to prepare the anode diffusion layer support layer, that is, a thin layer can be formed in advance, and then a support layer is further formed by stacking multiple thin layers. In this process, the thickness and porosity of the support layer are controllable. On the one hand, it is avoided that the porosity is too high, the fiber structure of the support layer is sparse, the electron transmission path is reduced, and the electrolysis efficiency is reduced; on the other hand, it is avoided that the porosity is too small, oxygen cannot be quickly removed, and large oxygen bubbles are formed, which then cover the catalyst surface and affect the catalytic electrolysis efficiency of water; in addition, through the preparation method of the present invention, the precious metal is adhered to the diffusion layer by immersion, and there is no need to prepare the catalyst layer by coating on the proton exchange membrane or other processes. Therefore, the present invention can completely avoid the swelling problem in the preparation process of the catalyst layer, so the preparation method of the present invention can be applied to the industrial development in the field of water electrolysis.

[0037] 2. The present invention adopts a multi-layer stacking method of multiple thin single-layer support layers. Compared with the method of directly adopting a thick single-layer, since the single-layer has a higher porosity, it is not conducive to the optimal ratio transmission of gas and liquid, and since the mechanical strength of the single-layer is not enough to support the high pressure during operation, it is easy to cause the anode diffusion layer to break, thereby damaging the membrane electrode and affecting the use of the entire electrolyzer. Therefore, the single-layer preparation needs to be set to a higher thickness. At this time, the fiber laying is uneven during the single-layer preparation process, resulting in uneven porosity distribution of the prepared anode diffusion layer, affecting gas and liquid transmission, resulting in increased resistance. Therefore, the present invention adopts a multi-layer stacking form. On the one hand, the porosity can be controlled within a suitable range. On the other hand, the prepared anode diffusion layer has a higher mechanical strength, plays a supporting role, and meets the mechanical strength requirements during the operation of the water electrolyzer. Therefore, the multi-layer structure has a higher porosity, which can effectively improve the transmission of water and gas between layers while meeting the mechanical strength requirements;

[0038] 3. The present invention uses a high-speed cutting machine to cut titanium dioxide nanotubes into short pieces at high speed. The cutting size is controllable and is just cut into a size suitable for preparing the anode diffusion layer, thereby avoiding the titanium dioxide nanotubes being too long and easily cutting the proton exchange membrane. At the same time, if the cutting size is too small, the prepared anode diffusion layer is easily dispersed and damaged, that is, the molding ability is poor.

[0039] 4. The present invention soaks the support layer in a chloride solution containing precious metals so that precious metal ions are uniformly adhered to its surface, and then undergoes high-temperature oxygenation molding, so that the precious metal ions are uniformly precipitated on the surface of the rutile titanium dioxide nanotubes. During high-temperature calcination containing oxygen, precious metal oxides are generated due to the presence of oxygen, and solid-phase reactions occur at high temperatures to embed them on the surface of the rutile titanium dioxide nanotubes, forming a dense catalytic conductive network structure. This structure is not easy to fall off under mechanical force and high and low temperature changes. Therefore, the preparation method of the present invention effectively improves the utilization rate of the catalytic reaction and the stability of the traditional CCM catalyst on the surface of the proton exchange membrane;

[0040] In addition, the present invention adopts the method of impregnation-high temperature oxidation to prepare the precious metal catalyst on the surface of the anode diffusion layer. On the one hand, the precious metal forms a dense metal oxide layer on the fiber of the anode diffusion layer, and the active sites of the precious metal catalyst are exposed to the outside, thereby improving the reaction efficiency of the precious metal catalyst, thereby reducing the precious metal loading and further reducing the cost. On the other hand, since the precious metal forms a network structure on the diffusion layer, there is no need to re-prepare the catalyst layer on the surface of the proton exchange membrane, thereby reducing the thickness of the entire membrane electrode, thereby improving the volume power density of the electrolyzer;

[0041] 5. When preparing the membrane electrode, the present invention sprays a layer of short side chain perfluorosulfonic acid resin on the surface of the prepared anode diffusion layer, which, on the one hand, makes the anode diffusion layer containing the catalyst and the proton exchange membrane more tightly combined during pressing, and on the other hand, the short side chain perfluorosulfonic acid resin can improve the proton conductivity to a greater extent, effectively reducing the contact resistance between the anode diffusion layer containing the catalyst and the proton exchange membrane;

[0042] 6. In the preparation of the precious metal catalyst network, the present invention can select two precious metals, iridium and ruthenium, with excellent catalytic performance, and appropriately adjust the ratio between the two, thereby saving costs and improving the catalytic performance. Moreover, since the precious metals are embedded in the surface of the diffusion layer, they are not easy to fall off, thereby improving the stability of the entire membrane electrode.

[0043] The concept, specific structure and technical effects of the present invention will be further described below in conjunction with the accompanying drawings to fully understand the purpose, characteristics and effects of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 It is a schematic diagram of the three-dimensional structure of the oxygen-containing calcination platform;

[0045] In the figure:

[0046] 1. Air source pipeline; 2. Microporous heating plate; 3. Ventilation hole; 4. Rutile titanium dioxide nanotube fiber layer; 5. Heat-insulating sealing box; 6. Gap; 7. Switch door; 8. Transmission main box; 9. Storage compartment. DETAILED DESCRIPTION

[0047] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0048] In the drawings, components with the same structure are indicated by the same numerical reference numerals, and components with similar structures or functions are indicated by similar numerical reference numerals. The size and thickness of each component shown in the drawings are arbitrarily shown, and the present invention does not limit the size and thickness of each component. In order to make the illustration clearer, the thickness of the components is appropriately exaggerated in some places in the drawings.

[0049] The structure of the oxygen-containing calcined platform suitable for the fiber layer in the following examples and comparative examples is as follows: Figure 1As shown, it includes a heat-insulating sealed box 5 with a switch door 7, two microporous heating plates 2 arranged parallel to each other are arranged in the heat-insulating sealed box 5, a plurality of ventilation holes 3 are arrayed on the microporous heating plates 2, a storage compartment 9 for placing rutile titanium dioxide nanotube fiber layers 4 in parallel is arranged between the two microporous heating plates 2, and at least two air source pipes 1 communicating with the inside of the heat-insulating sealed box 5 are arranged on the heat-insulating sealed box 5. After the gas in the air source pipe 1 enters the heat-insulating sealed box 5, it passes through the ventilation holes 3 on the microporous heating plates 2 and acts on the rutile titanium dioxide nanotube fiber layer 4, so that the rutile titanium dioxide nanotube fiber layer after impregnation and stacking is shaped and calcined in an oxygen-containing environment.

[0050] The microporous heating plate 2 is connected to the transmission main box 8, and a transmission mechanism is provided in the transmission main box 8. The microporous heating plate 2 realizes the lifting movement in the heat-insulating sealing box 5 through the transmission mechanism in the transmission main box 8. The two microporous heating plates 2 are driven by the transmission mechanism to make lifting movements in opposite directions, which can increase the space of the storage compartment 9 for the convenience of placing the rutile titanium dioxide nanotube fiber layer; the two microporous heating plates 2 are driven by the transmission mechanism to make lifting movements in opposite directions, which can gradually reduce the space of the storage compartment 9 and contact with the rutile titanium dioxide nanotube fiber layer to realize the clamping and hot pressing of the titanium dioxide nanotube fiber layer.

[0051] The transmission mechanism includes but is not limited to a drive motor, a screw rod, and a gear rack transmission group.

[0052] At least two gas source pipelines 1 are provided, and are respectively arranged at the upper top and the lower bottom of the heat-insulating sealing box 5 , and are respectively connected to the two microporous heating plates 2 .

[0053] When the two microporous heating plates 2 clamp and heat the titanium dioxide nanotube fiber layer, there are gaps 6 between the microporous heating plates 2 and the upper and lower inner walls of the heat-insulating sealing box 5, respectively, to facilitate smooth passage of gas.

[0054] The papermaking forming process applicable to the following embodiments and comparative examples is as follows:

[0055] (1) Pulping: Blending and stirring the fiber material, binder and dispersant, adjusting the ratio and viscosity, and forming a uniform slurry;

[0056] (2) Screen: Place the screen into the slurry and move it quickly to form a uniform fiber layer on the surface of the screen. Repeat the operation several times, lift the screen and drain the solvent.

[0057] (3) Peeling off: peeling off the screen and fiber layer in step (2);

[0058] (4) Drying: After the fiber layer is heated and dried, the desired single-layer thin paper is obtained.

[0059] Embodiment 1:

[0060] 1. Weigh 20g of 36.5wt.% concentrated hydrochloric acid and add it to 53g of deionized water to prepare a 10wt.% hydrochloric acid solution for later use;

[0061] 2. Weigh 5 g of titanium dioxide nanotubes with a diameter of 20 nm and a length of 50 mm and place them in the prepared hydrochloric acid solution, perform intermittent ultrasonic treatment for 10 min, with an intermittent frequency of 2 minutes, and let stand for 1 min;

[0062] 3. Soak the titanium dioxide nanotubes after ultrasonic acid washing in deionized water for 3 times, then rinse them in running water for 3 minutes, and soak the cleaned titanium dioxide nanotubes in ethanol for later use;

[0063] 4. Cut the cleaned titanium dioxide nanotubes into short pieces and cut them into a size of 1 mm in length;

[0064] 5. Place the chopped titanium dioxide nanotubes in a nitrogen-filled high-temperature calcining furnace, set the temperature to 1200°C, and calcine for 6 hours to form rutile titanium dioxide nanotubes;

[0065] 6. The calcined rutile titanium dioxide nanotubes were placed in a beaker, and 15 g of ethanol, 20 g of 25 wt.% PTFE emulsion and 75 g of deionized water were added, and ultrasonically mixed for 40 min to form a rutile titanium dioxide nanotube slurry for later use;

[0066] 7. The prepared slurry is prepared into a titanium dioxide nanotube fiber base paper with a wet thickness of 30 μm using conventional papermaking technology, and dried at 80° C. to form a rutile titanium dioxide nanotube fiber layer with a thickness of 10 μm and a porosity of 90% after drying;

[0067] 8. Weigh 4.5 g of chloroiridic acid hexahydrate and 1.5 g of ruthenium chloride trihydrate and dissolve them in 14 g of deionized water to form a 30 wt.% noble metal solution, prepare a 0.5 mol / L sodium hydroxide solution, adjust the solution pH to 7.5 by dropwise addition, and then immerse the rutile titanium dioxide nanotube fiber layer with a porosity of 90% in the noble metal solution for 10 min;

[0068] 9. The impregnated rutile titanium dioxide nanotube fiber layer was stacked into 7 layers and placed in an oxygen-containing calcination platform. The temperature was set at 300°C, the pressure was 0.5MPa, the oxygen flow rate was 5L / min, and the heat preservation was carried out for 4 hours to prepare a precious metal iridium with a loading of 1.2mg / cm 2 The loading of ruthenium metal is 0.4 mg / cm 2 , an anode diffusion layer (current collecting layer) having a catalyst network structure with a porosity of 80%;

[0069] 10. 20%wt.% of short side chain perfluorosulfonic acid resin with side chain molecular structure of -OCF2CF2SO3H was prepared into a 7wt.% resin solution and sprayed on the surface of the prepared anode diffusion layer (collecting layer) with catalyst network structure to form a resin loading of 9mg / cm 2 and then roll-compounded with a proton exchange membrane having a catalyst layer at the cathode, wherein a pressure of 0.3 MPa is set to obtain a membrane electrode having a diffusion layer (collecting layer) at the anode.

[0070] Embodiment 2:

[0071] 1. Weigh 40g of 36.5wt.% concentrated hydrochloric acid and add it to 18.4g of deionized water to prepare a 25wt.% hydrochloric acid solution for later use;

[0072] 2. Weigh 10g of titanium dioxide nanotubes with a diameter of 20nm and a length of 50mm and place them in the prepared hydrochloric acid solution, perform intermittent ultrasonic treatment for 30min, with an intermittent frequency of 2min, and let stand for 1min;

[0073] 3. Soak the titanium dioxide nanotubes after ultrasonic acid washing in deionized water for 5 times, then rinse them with running water for 5 minutes, and soak the washed titanium dioxide nanotubes in ethanol for later use;

[0074] 4. Cut the cleaned titanium dioxide nanotubes into short pieces and cut them into a size of 5 mm in length;

[0075] 5. Place the short-cut titanium dioxide nanotubes in a nitrogen-filled high-temperature calcining furnace, set the temperature to 1500°C, and calcine for 4 hours to form rutile titanium dioxide nanotubes;

[0076] 6. The calcined rutile titanium dioxide nanotubes were placed in a beaker, and 80 g of isopropanol, 120 g of 25 wt.% PTFE emulsion and 220 g of deionized water were added, and ultrasonic mixing was performed for 60 min to form a rutile titanium dioxide nanotube slurry liquid for later use;

[0077] 7. The prepared slurry is prepared into a titanium dioxide nanotube fiber base paper with a wet thickness of 60 μm using conventional papermaking technology, and dried at 120° C. to form a rutile titanium dioxide nanotube fiber layer with a thickness of 30 μm after drying and a porosity of 70%;

[0078] 8. Weigh 15 g of chloroiridic acid hexahydrate and 5 g of ruthenium chloride trihydrate and dissolve them in 13.3 g of deionized water to form a 60 wt.% noble metal solution, prepare a 0.8 mol / L sodium hydroxide solution, adjust the solution pH to 8.5 by dropwise addition, and then immerse the rutile titanium dioxide nanotube fiber layer with a porosity of 70% in the noble metal solution for 30 min;

[0079] 9. The impregnated rutile titanium dioxide nanotube fiber layer was stacked into 4 layers and placed in an oxygen-containing calcination platform. The temperature was set to 400°C, the pressure was 2MPa, the air flow rate was 10L / min, and the hot pressing was carried out for 2h to prepare a precious metal iridium with a loading of 0.8mg / cm 2 The loading of ruthenium metal is 0.2 mg / cm 2 , an anode diffusion layer (current collecting layer) having a catalyst network structure with a porosity of 60%;

[0080] 10. 20%wt.% of short side chain perfluorosulfonic acid resin with side chain molecular structure of -OCF2CF2CF2SO3H was prepared into a 3wt.% resin solution and sprayed on the surface of the prepared anode diffusion layer (collecting layer) with catalyst network structure to form a resin loading of 6mg / cm 2 and then roll-compounded with a proton exchange membrane having a catalyst layer at the cathode, wherein a pressure of 0.5 MPa is set to obtain a membrane electrode having a diffusion layer (collecting layer) at the anode.

[0081] Embodiment 3:

[0082] 1. Weigh 18g of 36.5wt.% concentrated hydrochloric acid and add it to 18.5g of deionized water to prepare an 18wt.% hydrochloric acid solution for later use;

[0083] 2. Weigh 8 g of titanium dioxide nanotubes with a diameter of 30 nm and a length of 50 mm and place them in the prepared hydrochloric acid solution, perform intermittent ultrasonic treatment for 20 min, with an intermittent frequency of 2 minutes, and let stand for 1 min;

[0084] 3. Soak the titanium dioxide nanotubes after ultrasonic acid washing in deionized water for 4 times, then rinse them with running water for 4 minutes, and soak the washed titanium dioxide nanotubes in ethanol for later use;

[0085] 4. Cut the cleaned titanium dioxide nanotubes into short pieces and cut them into a size of 3 mm in length;

[0086] 5. Place the chopped titanium dioxide nanotubes in a nitrogen-filled high-temperature calcining furnace, set the temperature to 1300°C, and calcine for 5 hours to form rutile titanium dioxide nanotubes;

[0087] 6. The calcined rutile titanium dioxide nanotubes were placed in a beaker, and 48 g of n-propanol, 64 g of 25 wt.% PTFE emulsion and 160 g of deionized water were added, and ultrasonically mixed for 50 min to form a rutile titanium dioxide nanotube slurry for later use;

[0088] 7. A slurry prepared by conventional papermaking technology is used to prepare a titanium dioxide nanotube fiber base paper with a wet thickness of 30 μm, which is dried at 80° C. to form a rutile titanium dioxide nanotube fiber layer with a thickness of 20 μm and a porosity of 80% after drying;

[0089] 8. Weigh 9 g of chloroiridic acid hexahydrate and 3 g of ruthenium chloride trihydrate and dissolve them in 18 g of deionized water to form a noble metal solution with a concentration of 40 wt.%, prepare a sodium hydroxide solution with a concentration of 0.6 mol / L, adjust the solution pH to 8 by dropwise addition, and then immerse the rutile titanium dioxide nanotube fiber layer with a porosity of 80% in the noble metal solution for 20 min;

[0090] 9. The impregnated rutile titanium dioxide nanotube fiber layer was stacked into 5 layers and placed in an oxygen-containing calcination platform. The temperature was set to 350°C, the pressure was 1MPa, the oxygen flow rate was 7L / min, and the heat was kept for 3 hours. The precious metal iridium loading was 1mg / cm 2 The loading of ruthenium metal is 0.3 mg / cm 2 , an anode diffusion layer (current collecting layer) having a catalyst network structure with a porosity of 70%;

[0091] 10. 20%wt.% of short side chain perfluorosulfonic acid resin with side chain molecular structure of -OCF2SO3H was prepared into a 5wt.% resin solution and sprayed on the surface of the prepared anode diffusion layer (collecting layer) with catalyst network structure to form a resin loading of 8mg / cm 2 and then roll-compounded with a proton exchange membrane having a catalyst layer at the cathode, wherein a pressure of 0.4 MPa is set to obtain a membrane electrode having a diffusion layer (collecting layer) at the anode.

[0092] Comparative Example 1: (TiO2 nanotubes are not short-cut)

[0093] 1. Weigh 20g of 36.5wt.% concentrated hydrochloric acid and add it to 53g of deionized water to prepare a 10wt.% hydrochloric acid solution for later use;

[0094] 2. Weigh 5 g of titanium dioxide nanotubes with a diameter of 20 nm and a length of 50 mm and place them in the prepared hydrochloric acid solution, perform intermittent ultrasonic treatment for 10 min, with an intermittent frequency of 2 minutes, and let stand for 1 min;

[0095] 3. Soak the titanium dioxide nanotubes after ultrasonic acid washing in deionized water for 3 times, then rinse them in running water for 3 minutes, and soak the cleaned titanium dioxide nanotubes in ethanol for later use;

[0096] 4. The cleaned titanium dioxide nanotubes soaked in ethanol are placed in a nitrogen-filled high-temperature calcining furnace, and the temperature is set to 1200°C and the time is 6 hours for high-temperature calcination to form rutile titanium dioxide nanotubes;

[0097] 5. The calcined rutile titanium dioxide nanotubes were placed in a beaker, and 15 g of ethanol, 20 g of 25 wt.% PTFE emulsion and 75 g of deionized water were added, and ultrasonically mixed for 40 min to form a rutile titanium dioxide nanotube slurry for later use;

[0098] 6. The prepared slurry is prepared into a titanium dioxide nanotube fiber base paper with a wet thickness of 30 μm using conventional papermaking technology, and dried at 80° C. to form a rutile titanium dioxide nanotube fiber layer with a thickness of 10 μm and a porosity of 90% after drying;

[0099] 7. Weigh 4.5 g of iridic acid hexahydrate and 1.5 g of ruthenium chloride trihydrate and dissolve them in 14 g of deionized water to form a 30 wt.% noble metal solution, prepare a 0.5 mol / L sodium hydroxide solution, adjust the solution pH to 7.5 by dropwise addition, and then immerse the rutile titanium dioxide nanotube fiber layer with a porosity of 90% in the noble metal solution for 10 min;

[0100] 8. The impregnated rutile titanium dioxide nanotube fiber layer was stacked into 7 layers and placed in an oxygen-containing calcination platform. The temperature was set at 300°C, the pressure was 0.5MPa, the oxygen flow rate was 5L / min, and the heat preservation was carried out for 4 hours to prepare a precious metal iridium with a loading of 1.2mg / cm 2 The loading of ruthenium metal is 0.4 mg / cm 2 , an anode diffusion layer (current collecting layer) having a catalyst network structure with a porosity of 80%;

[0101] 9. Prepare 7 wt. % of a short side chain perfluorosulfonic acid resin with a side chain molecular structure of -OCF2CF2SO3H into a resin solution, spray it on the surface of the prepared anode diffusion layer (collecting layer) with a catalyst network structure to form a resin layer with a resin loading of 9 mg / cm2; then roll-compound it with a proton exchange membrane with a catalyst layer at the cathode, wherein the pressure is set to 0.3 MPa, to obtain a membrane electrode with an anode diffusion layer (collecting layer).

[0102] Comparative Example 2: (Titanium dioxide nanotubes are not calcined to rutile type)

[0103] 1. Weigh 20g of 36.5wt.% concentrated hydrochloric acid and add it to 53g of deionized water to prepare a 10wt.% hydrochloric acid solution for later use;

[0104] 2. Weigh 5 g of titanium dioxide nanotubes with a diameter of 20 nm and a length of 50 mm and place them in the prepared hydrochloric acid solution, perform intermittent ultrasonic treatment for 10 min, with an intermittent frequency of 2 minutes, and let stand for 1 min;

[0105] 3. Soak the titanium dioxide nanotubes after ultrasonic acid washing in deionized water for 3 times, then rinse them in running water for 3 minutes, and soak the cleaned titanium dioxide nanotubes in ethanol for later use;

[0106] 4. Cut the cleaned titanium dioxide nanotubes into short pieces and cut them into a size of 1 mm in length;

[0107] 5. Place the chopped titanium dioxide nanotubes in a beaker, add 15 g of ethanol, 20 g of 25 wt.% PTFE emulsion and 75 g of deionized water, and mix them by ultrasonic for 40 min to form a rutile titanium dioxide nanotube slurry for later use;

[0108] 6. The prepared slurry was prepared into a titanium dioxide nanotube fiber base paper with a wet thickness of 30 μm using conventional papermaking technology, and dried at 80° C. to form a titanium dioxide nanofiber layer with a thickness of 10 μm and a porosity of 90% after drying;

[0109] 7. Weigh 4.5 g of chloroiridic acid hexahydrate and 1.5 g of ruthenium chloride trihydrate and dissolve them in 14 g of deionized water to form a 30 wt.% noble metal solution, prepare a 0.5 mol / L sodium hydroxide solution, adjust the solution pH to 7.5 by dropping, and then immerse the titanium dioxide nanofiber layer with a porosity of 90% in the noble metal solution for 10 min;

[0110] 8. The impregnated titanium dioxide nanofiber layer was stacked into 7 layers and placed in an oxygen-containing calcination platform. The temperature was set at 300°C, the pressure was 0.5 MPa, the oxygen flow rate was 5 L / min, and the heat preservation was carried out for 4 hours to prepare a precious metal iridium with a loading of 1.2 mg / cm 2 The loading of ruthenium metal is 0.4 mg / cm 2 , an anode diffusion layer (current collecting layer) having a catalyst network structure with a porosity of 80%;

[0111] 9. Prepare 7 wt. % of a short side chain perfluorosulfonic acid resin with a side chain molecular structure of -OCF2CF2SO3H into a resin solution, spray it on the surface of the prepared anode diffusion layer (collecting layer) with a catalyst network structure to form a resin layer with a resin loading of 9 mg / cm2; then roll-compound it with a proton exchange membrane with a catalyst layer at the cathode, wherein the pressure is set to 0.3 MPa, to obtain a membrane electrode with an anode diffusion layer (collecting layer).

[0112] Comparative Example 3: (Do not spray short side chain resin)

[0113] 1. Weigh 20g of 36.5wt.% concentrated hydrochloric acid and add it to 53g of deionized water to prepare a 10wt.% hydrochloric acid solution for later use;

[0114] 2. Weigh 5 g of titanium dioxide nanotubes with a diameter of 20 nm and a length of 50 mm and place them in the prepared hydrochloric acid solution, perform intermittent ultrasonic treatment for 10 min, with an intermittent frequency of 2 minutes, and let stand for 1 min;

[0115] 3. Soak the titanium dioxide nanotubes after ultrasonic acid washing in deionized water for 3 times, then rinse them in running water for 3 minutes, and soak the cleaned titanium dioxide nanotubes in ethanol for later use;

[0116] 4. Cut the cleaned titanium dioxide nanotubes into short pieces and cut them into a size of 1 mm in length;

[0117] 5. Place the chopped titanium dioxide nanotubes in a nitrogen-filled high-temperature calcining furnace, set the temperature to 1200°C, and calcine for 6 hours to form rutile titanium dioxide nanotubes;

[0118] 6. The calcined rutile titanium dioxide nanotubes were placed in a beaker, and 15 g of ethanol, 20 g of 25 wt.% PTFE emulsion and 75 g of deionized water were added, and ultrasonically mixed for 40 min to form a rutile titanium dioxide nanotube slurry for later use;

[0119] 7. The prepared slurry is prepared into a titanium dioxide nanotube fiber base paper with a wet thickness of 30 μm using conventional papermaking technology, and dried at 80° C. to form a rutile titanium dioxide nanotube fiber layer with a thickness of 10 μm and a porosity of 90% after drying;

[0120] 8. Weigh 4.5 g of chloroiridic acid hexahydrate and 1.5 g of ruthenium chloride trihydrate and dissolve them in 14 g of deionized water to form a 30 wt.% noble metal solution, prepare a 0.5 mol / L sodium hydroxide solution, adjust the solution pH to 7.5 by dropwise addition, and then immerse the rutile titanium dioxide nanotube fiber layer with a porosity of 90% in the noble metal solution for 10 min;

[0121] 9. The impregnated rutile titanium dioxide nanotube fiber layer was stacked into 7 layers and placed in an oxygen-containing calcination platform. The temperature was set at 300°C, the pressure was 0.5MPa, the oxygen flow rate was 5L / min, and the heat preservation was carried out for 4 hours to prepare a precious metal iridium with a loading of 1.2mg / cm 2 The loading of ruthenium metal is 0.4 mg / cm 2 , an anode diffusion layer (current collecting layer) having a catalyst network structure with a porosity of 80%;

[0122] 10. The prepared anode diffusion layer (collecting layer) and cathode proton exchange membrane with catalyst layer are rolled and compounded, wherein the pressure is set to 0.3 MPa, to obtain a membrane electrode with anode diffusion layer (collecting layer).

[0123] Comparative Example 4: (No air or oxygen is introduced during the diffusion layer molding, and inert gas is used)

[0124] 1. Weigh 20g of 36.5wt.% concentrated hydrochloric acid and add it to 53g of deionized water to prepare a 10wt.% hydrochloric acid solution for later use;

[0125] 2. Weigh 5 g of titanium dioxide nanotubes with a diameter of 20 nm and a length of 50 mm and place them in the prepared hydrochloric acid solution, perform intermittent ultrasonic treatment for 10 min, with an intermittent frequency of 2 minutes, and let stand for 1 min;

[0126] 3. Soak the titanium dioxide nanotubes after ultrasonic acid washing in deionized water for 3 times, then rinse them in running water for 3 minutes, and soak the cleaned titanium dioxide nanotubes in ethanol for later use;

[0127] 4. Cut the cleaned titanium dioxide nanotubes into short pieces and cut them into a size of 1 mm in length;

[0128] 5. Place the chopped titanium dioxide nanotubes in a nitrogen-filled high-temperature calcining furnace, set the temperature to 1200°C, and calcine for 6 hours to form rutile titanium dioxide nanotubes;

[0129] 6. The calcined rutile titanium dioxide nanotubes were placed in a beaker, and 15 g of ethanol, 20 g of 25 wt.% PTFE emulsion and 75 g of deionized water were added, and ultrasonically mixed for 40 min to form a rutile titanium dioxide nanotube slurry for later use;

[0130] 7. The prepared slurry is prepared into a titanium dioxide nanotube fiber base paper with a wet thickness of 30 μm using conventional papermaking technology, and dried at 80° C. to form a rutile titanium dioxide nanotube fiber layer with a thickness of 10 μm and a porosity of 90% after drying;

[0131] 8. Weigh 4.5 g of chloroiridic acid hexahydrate and 1.5 g of ruthenium chloride trihydrate and dissolve them in 14 g of deionized water to form a 30 wt.% noble metal solution, prepare a 0.5 mol / L sodium hydroxide solution, adjust the solution pH to 7.5 by dropwise addition, and then immerse the rutile titanium dioxide nanotube fiber layer with a porosity of 90% in the noble metal solution for 10 min;

[0132] 9. The impregnated rutile titanium dioxide nanotube fiber layer was stacked into 7 layers and placed in an oxygen-containing calcination platform. The temperature was set to 300°C, the pressure was 0.5 MPa, the flow rate of inert gas nitrogen was 5 L / min, and the heat preservation was carried out for 4 hours to prepare a precious metal iridium with a loading of 1.2 mg / cm 2 The loading of ruthenium metal is 0.4 mg / cm 2 , an anode diffusion layer (current collecting layer) having a catalyst network structure with a porosity of 80%;

[0133] 10. Prepare 7 wt. % of a short side chain perfluorosulfonic acid resin with a side chain molecular structure of -OCF2CF2SO3H into a resin solution, spray it on the surface of the prepared anode diffusion layer (collecting layer) with a catalyst network structure to form a resin layer with a resin loading of 9 mg / cm2; then roll-compound it with a proton exchange membrane with a catalyst layer at the cathode, wherein the pressure is set to 0.3 MPa, to obtain a membrane electrode with an anode diffusion layer (collecting layer).

[0134] Comparative Example 5: (directly a thicker single layer as a support layer)

[0135] 1. Weigh 20g of 36.5wt.% concentrated hydrochloric acid and add it to 53g of deionized water to prepare a 10wt.% hydrochloric acid solution for later use;

[0136] 2. Weigh 5 g of titanium dioxide nanotubes with a diameter of 20 nm and a length of 50 mm and place them in the prepared hydrochloric acid solution, perform intermittent ultrasonic treatment for 10 min, with an intermittent frequency of 2 minutes, and let stand for 1 min;

[0137] 3. Soak the titanium dioxide nanotubes after ultrasonic acid washing in deionized water for 3 times, then rinse them in running water for 3 minutes, and soak the cleaned titanium dioxide nanotubes in ethanol for later use;

[0138] 4. Cut the cleaned titanium dioxide nanotubes into short pieces and cut them into a size of 1 mm in length;

[0139] 5. Place the chopped titanium dioxide nanotubes in a nitrogen-filled high-temperature calcining furnace, set the temperature to 1200°C, and calcine for 6 hours to form rutile titanium dioxide nanotubes;

[0140] 6. The calcined rutile titanium dioxide nanotubes were placed in a beaker, and 15 g of ethanol, 20 g of 25 wt.% PTFE emulsion and 75 g of deionized water were added, and ultrasonically mixed for 40 min to form a rutile titanium dioxide nanotube slurry for later use;

[0141] 7. The prepared slurry is prepared into a titanium dioxide nanotube fiber base paper with a wet thickness of 210 μm using conventional papermaking technology, and dried at 80° C. to form a rutile titanium dioxide nanotube fiber layer with a thickness of 70 μm and a porosity of 90% after drying;

[0142] 8. Weigh 4.5 g of chloroiridic acid hexahydrate and 1.5 g of ruthenium chloride trihydrate and dissolve them in 14 g of deionized water to form a 30 wt.% noble metal solution, prepare a 0.5 mol / L sodium hydroxide solution, adjust the solution pH to 7.5 by dropwise addition, and then immerse the rutile titanium dioxide nanotube fiber layer with a porosity of 90% in the noble metal solution for 10 min;

[0143] 9. The impregnated rutile titanium dioxide nanotube fiber layer was placed in an oxygen-containing calcination platform, set the temperature to 300°C, the pressure to 0.5 MPa, the oxygen flow rate to 5 L / min, and hot press for 4 hours to prepare a precious metal iridium with a loading of 1.2 mg / cm 2 The loading of ruthenium metal is 0.4 mg / cm 2 , an anode diffusion layer (current collecting layer) having a catalyst network structure with a porosity of 80%;

[0144] 10. Prepare 7 wt. % of a short side chain perfluorosulfonic acid resin with a side chain molecular structure of -OCF2CF2SO3H into a resin solution, spray it on the surface of the prepared anode diffusion layer (collecting layer) with a catalyst network structure to form a resin layer with a resin loading of 9 mg / cm2; then roll-compound it with a proton exchange membrane with a catalyst layer at the cathode, wherein the pressure is set to 0.3 MPa, to obtain a membrane electrode with an anode diffusion layer (collecting layer).

[0145] The electrochemical performance results of the membrane electrodes prepared in the examples and comparative examples are shown in Table 1.

[0146] Table 1 Membrane electrode electrolysis current density table

[0147]

[0148]

[0149] As shown in Table 1, the anode diffusion layer for water electrolysis prepared by the present invention has a catalyst network structure prepared on the anode diffusion layer. When assembling into a membrane electrode, it is not necessary to prepare a catalyst layer on the proton exchange membrane. The membrane electrode prepared by the present invention has a low noble metal loading and excellent electrochemical activity. At an electrolysis voltage of 2.0 V, its current density is 1800 mA / cm 2 above.

[0150] In the comparative examples, in comparative example 1, the titanium dioxide nanotubes were not cut short when preparing the anode diffusion layer, and the longer titanium dioxide nanotubes could not remove the gas in time, resulting in obstruction of mass transfer, so the performance was lower than that of the embodiment; in comparative example 2, the titanium dioxide nanotubes were not calcined at high temperature to be rutile titanium dioxide, and due to the high resistance of titanium dioxide, the prepared anode diffusion layer had a large impedance and poor electrochemical performance; in the process of preparing the membrane electrode in comparative example 3, the resin solution was not sprayed on the anode diffusion layer, and the prepared membrane electrode had incomplete contact between the anode diffusion layer and the proton exchange membrane. There are gaps, so the interface resistance is high, and proton conduction is hindered, and the performance is poor; in the process of preparing the anode diffusion layer in Comparative Example 4, no air or oxygen is introduced during hot pressing, and an inert gas is used. The precious metal ions on the prepared anode diffusion layer are not oxidized, which causes the precious metal to fall off and lose easily. The electrolytic performance is good at the beginning, but drops sharply with the passage of time; in Comparative Example 5, the anode diffusion layer is prepared by one-time molding. The prepared diffusion layer has uneven pore distribution, which causes electron and gas transmission to be hindered, affecting its electrolytic efficiency, and the electrolytic performance is poor.

[0151] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

Claims

1. A method for preparing a PEM water electrolysis membrane electrode, characterized in that: The following steps are involved: Step 1: Cleaning the titanium dioxide nanotubes; Step 2: chopping the titanium dioxide nanotubes cleaned in step 1 into short pieces, and then calcining them in an inert gas atmosphere to form rutile titanium dioxide nanotubes; Step 3: Put the rutile titanium dioxide nanotubes into a container, add a dispersant, a binder and deionized water, and perform ultrasonic dispersion to obtain a rutile titanium dioxide nanotube slurry; Step 4: Using a papermaking process, the rutile titanium dioxide nanotube slurry obtained in step 3 is molded. A rutile titanium dioxide nanotube fiber base paper is prepared, and a rutile titanium dioxide nanotube fiber layer is formed after drying; Step 5: dissolving hexahydrated iridium chloride H2IrCl6·6H2O and trihydrated ruthenium chloride RuCl3·3H2O in deionized water to obtain a precious metal solution, placing the rutile titanium dioxide nanotube fiber layer obtained in step 4 into the precious metal solution, adding an alkaline solution, controlling the pH to be greater than 7, removing the fiber layer after immersion, and stacking the impregnated single-layer rutile titanium dioxide nanotube fiber layer in N layers, where N is greater than 1. After stacking, pressurizing the fiber layer and placing the fiber layer in an oxygen-containing environment for finalizing and calcining to form a current collecting layer having a catalyst layer of a mixture of iridium oxide and ruthenium oxide; Step 6: Composite roll-press the current collecting layer with the iridium oxide and ruthenium oxide mixture catalyst layer obtained in step 5 and the proton exchange membrane with the catalyst layer at the cathode to obtain a PEM water electrolysis membrane electrode with the current collecting layer at the anode.

2. The method for preparing a PEM water electrolysis membrane electrode according to claim 1, characterized in that: In step 1, the specific steps of cleaning the titanium dioxide nanotubes are: (1) preparing a hydrochloric acid solution with a concentration of 10-25wt.%; (2) placing the titanium dioxide nanotubes in a hydrochloric acid solution, intermittently sonicating for 10-30 minutes, with an intermittent frequency of 2 minutes of sonication, and standing for 1 minute; (3) Soaking the titanium dioxide nanotubes after ultrasonic acid washing in deionized water for 3-5 times, and rinsing them in running deionized water for 3-5 minutes; (4) Soaking the cleaned titanium dioxide nanotubes in an alcohol solvent to prevent contamination; the alcohol solvent is methanol, ethanol or n-propanol.

3. The method for preparing a PEM water electrolysis membrane electrode according to claim 1, characterized in that: The diameter of the titanium dioxide nanotubes is 20-50 nm. In step 2, the length of the short-cut titanium dioxide nanotubes is 1-5 mm. The inert gas is nitrogen, argon or helium. The calcination is carried out in a high-temperature calcination furnace at a temperature of 1200-1500° C. for 4-6 hours.

4. The method for preparing a PEM water electrolysis membrane electrode according to claim 1, characterized in that: In step three, the mass ratio of rutile titanium dioxide nanotubes: dispersant: binder: deionized water is 1:3-8:1-3:15-22; the dispersant is one of ethanol, methanol, n-propanol, isopropanol, and n-butanol; the binder is 25wt.% PTFE emulsion; and the ultrasonic mixing time is 40-60min.

5. The method for preparing a PEM water electrolysis membrane electrode according to claim 1, characterized in that: In step 4, the wet thickness of the rutile titanium dioxide nanotube fiber base paper is 30-60 μm; the drying temperature is 80-120° C.; the thickness of the rutile titanium dioxide nanotube fiber layer after drying is 10-30 μm, and the porosity is 70-90%.

6. The method for preparing a PEM water electrolysis membrane electrode according to claim 1, characterized in that: In step five, the mass concentration of the precious metal solution is 30-60wt.%, the mass ratio of hexahydrate iridium chloride H2IrCl6·6H2O and trihydrate ruthenium chloride RuCl3·3H2O is 3:1; the alkaline solution is a sodium hydroxide solution with a concentration of 0.5-0.8 mol / L; the pH is controlled at 7.5-8.5; and the immersion time is 10-30 min.

7. The method for preparing a PEM water electrolysis membrane electrode according to claim 6, characterized in that: In step 5, the single-layer rutile titanium dioxide nanotube fiber layer is stacked in N layers, and the N value is 4-7; the shaping calcination temperature is 300-400°C, the calcination time is 2-4h, the pressure is 0.5-2MPa, and the porosity of the prepared collector layer is 60-80%; the metal iridium loading is 0.8-1.2mg / cm 2 The loading of ruthenium metal is 0.2-0.4 mg / cm 2 ; The flow rate of the oxygen-containing gas is 5-10L / min, and the oxygen-containing environment is an environment filled with air or oxygen.

8. The method for preparing a PEM water electrolysis membrane electrode according to any one of claims 1 to 7, characterized in that: In step 5, during calcination, the device for providing an oxygen-containing environment for the impregnated and stacked rutile titanium dioxide nanotube fiber layer is an oxygen-containing calcination platform, the oxygen-containing calcination platform comprises a heat-insulating sealed box (5) provided with a switch door (7), the heat-insulating sealed box (5) is provided with two microporous heating plates (2) arranged parallel to each other, the microporous heating plates (2) are arrayed with a plurality of vent holes (3), and a rutile titanium dioxide nanotube fiber layer is provided between the two microporous heating plates (2). (4) parallel storage compartments (9), the heat-insulating sealed box (5) is provided with at least two gas source pipes (1) communicating with the interior of the heat-insulating sealed box (5), after the gas in the gas source pipes (1) enters the heat-insulating sealed box (5), it passes through the vent holes (3) on the microporous heating plate (2) and acts on the rutile titanium dioxide nanotube fiber layer (4), so that the rutile titanium dioxide nanotube fiber layer after impregnation and stacking is shaped and calcined in an oxygen-containing environment.

9. The method for preparing a PEM water electrolysis membrane electrode according to claim 1, characterized in that: In step six, first prepare a short side chain perfluorosulfonic acid resin solution, wherein the side chain molecular structure of the short side chain perfluorosulfonic acid resin is one or more of -OCF2CF2SO3H, -OCF2CF2CF2SO3H, and -OCF2SO3H; and spray the short side chain perfluorosulfonic acid resin solution on the surface of the current collecting layer prepared in step five, and then composite roll-press the current collecting layer with the short side chain perfluorosulfonic acid resin solution on the surface and the proton exchange membrane with a catalyst layer at the cathode to obtain a PEM water electrolysis membrane electrode with a current collecting layer at the anode.

10. The method for preparing a PEM water electrolysis membrane electrode according to claim 9, characterized in that: In step 6, the concentration of the short side chain perfluorosulfonic acid resin solution is 3-7 wt.%; after the short side chain perfluorosulfonic acid resin solution is dried, the resin loading is 6-9 mg / cm 2 .

11. The method for preparing a PEM water electrolysis membrane electrode according to claim 1, 9 or 10, characterized in that: In step six, the pressure when the current collecting layer and the proton exchange membrane with the cathode catalyst layer are compositely rolled is 0.3-0.5 MPa.

Citation Information

Patent Citations

  • Titanium oxide nanostructures for fuel cell electrodes

    CN105122523A

  • Titanium fiber felt anode diffusion layer for PEM water electrolysis tank as well as preparation method and application thereof

    CN112647086A